Joint opportunistic approaches for building resilient information sharing toward heterogeneous networks integration - Batista, Agnaldo de Souza; Santos, Aldri Luiz dos (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
Massive networks demand resilient critical infrastructures as a means to achieve a safe operation against threats to their continuous and correct functioning. As a novelty, this thesis argues that the application of multi-opportunistic approaches can aid more robust information sharing on networks in the face of anomalies, and timeand space-sensitive data, thus enhancing overall resilience. To validate the hypothesis, we applied two opportunistic approaches jointly in a fixed environment on a collaborative network intrusion detection system (C-NIDS) for IoT networks against distributed denial-of-service (DDoS) attacks. Next, we employed two approaches on a location service in a network of unmanned aerial vehicles (UAVs) against false data injection (FDI) attacks. Thus, we evinced that a number of opportunistic approaches when employed jointly has great potential to provide resilient services across various network critical structures.